Evaluation of the visco-elastic properties in asphalt rubber in conventional mixtures - Minhoto, Manuel (2007)
Flexible pavements are subjected to a set of degradations on the pavement surface, such as cracks and other specific types of distress which arise from traffic and temperature variations and which are responsible for the users’ unsafety and discomfort. The occurrence of temperature variations in the pavement leads to a severe aggravation of the reflective cracking phenomenon what implies a premature distress of the overlays. In this way, a theoretical study about the influence of temperature variation in the reflective cracking overlay behaviour was performed. To this end, a thermo-mechanical characterization of bituminous materials was made through a set of tests performed with an asphalt rubber mix and a conventional mix. It is intended to study the relaxation behaviour for four different temperature cases, 25ºC, 15ºC, 5ºC and -5ºC, which is a range of temperature variations similar to those that occur in the pavements located in the Northeast of Portugal. This paper presents a study in which the viscoelastic properties of asphalt rubber and conventional mixes, related with long-time loading and thermal loading, were determined through static relaxation tests using different test configurations. It also describes the material used, the test configurations applied to evaluate the viscoelastic properties and it finally establishes a comparison between the two mixes studied.